IMPLEMENTATION OF CA - TECHNOLOGY IN TEACHING PREPARING FOR THE FUTURE - ŠMERINGAIOVÁ, Anna; PAVLENKO, Slavko (Trends in education, 2017)
The current trend of development, design and production in engineering industry is characterized by their strong support by various CA technologies. The aim of FVT TU Košice is the education of universally educated engineers who are capable to find a job in wide spectrum of engineering companies. The combination of professional knowledge, language skills, good computer skills and knowledge of using different CAx systems to solve technical problems increases the chances of school graduates employability. By implementation of CAD/CAM/CAE technology in the learning process students learn to use them actively for the construction and technological design and for solving various technical problems.
Keywords: CAD system; modeling; simulation; specialized laboratory